Integration of Behaviorist Theory in Islamic Character Building Students in Madrasah - Wardati, Laila; Ridha, Nikmatur; Misnan, Misnan (STAI Serdang Lubuk Pakam, 2025)
This study was motivated by the need to strengthen Islamic character education among madrasah students, especially amid the challenges of globalization that often weaken the moral values of adolescents. The objectives of this study are (1) to analyze the principles of behaviorism in strengthening Islamic character at MTs PAB VI Helvetia; (2) to identify the forms of reinforcement used by teachers; and (3) to analyze their effectiveness. This study used a qualitative approach with a case study method, through observation, interviews, and documentation. The results of the study indicate that the application of behaviorism principles has proven effective in shaping students' Islamic character. Stimulus-response practices are manifested in teachers' role modeling and religious habits, reinforcement is applied in the form of praise and educational reprimands, while conditioning is evident through religious routines and Islamic social interactions. The study's conclusions emphasize the importance of consistency, teacher modeling, and family support. The implications of this research are the need for synergy between schools, families, and communities in strengthening the continuous development of noble character among students.